Genetic Villains: Killer Meiotic Drivers - Bravo Núñez, María Angélica (Trends Genet, 2018)
Unbiased allele transmission into progeny is a fundamental genetic concept canonized as Mendel’s Law of Segregation. Not all alleles, however, abide by the law. Killer meiotic drivers are ultra-selfish DNA sequences that are transmitted into more than half (sometimes all) of the meiotic products generated by a heterozygote. As their name implies, these loci gain a transmission advantage in heterozygotes by destroying otherwise viable meiotic products that do not inherit the driver. We review and classify killer meiotic drive genes across a wide spectrum of eukaryotes. We discuss how analyses of these ultra-selfish genes can lead to greater insight into the mechanisms of gametogenesis and the causes of infertility.